Lithuanian rowers at the European Championship 2012 - Slisauskiene, L.; Sulniene, R. (Education. Physical training. Sport, 2012)
Research background and hypothesis. In rowing, not enough attention is paid to the peculiarities of distance pacing and race tactics. At the same time the annually increasing boat speeds and closeness among the results of the world and the European championship winners, the race tactics can be of decisive importance. Although many scientific articles on Lithuanian rowing have already been published, there are not enough scientific studies on the peculiarities of distance pacing of Lithuanian rowers. Research aim was to determine the peculiarities of distance pacing of Lithuanian rowers at the European championship 2012. Research methods. The following study methods were used: literature review and competition records analysis. In accordance with the technical records of the European championship 2012 (http://www.worldrowing.com/results/), the average speed in the distance and speed changes in different sections of 84 crews were analysed. The peculiarities of distance pacing and tactics variants of the Lithuanian men single scull, double scull and women single scull and the best European rowers were compared. Research results. Lithuanian rowers were the fastest in the first 500 m section of the distance and applied 1-3 and 1-4 tactical variants. The speed changes at the European championship 2012 were 1.70-2.69%. At the European championship 2012, the crews who took 4-6th places were more likely to exceed their average distance speed in the first section of the distance than the crews who took places 1-3 (p < 0.05). Discussion and conclusions. Speed changes in the distance of Lithuanian men single scull and double scull rowers were one of the lowest and the average pace was the highest compared to the records of other finalists. The speed changes in distance of women single scull rowers were among the highest while the average pace was the lowest compared to the records of other Final A participants. Although Lithuanian women single scull rowers had high speed changes in the distance and their rowing pace was low, high average speed in the whole distance allowed them winning at the European championship.